Pembentukan Karakter Santri melalui Habituasi Disiplin Kegiatan Pondok Di TMI Al-Amien Prenduan Sumenep - Darul Hikmah; Nurul Zainab; Buna'i Buna'i (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
Character education is a substantial part of the Islamic education system. Observing a number of recent viral incidents with the fact that the moral decline of the nation's children is caused by one of them many Indonesian schools which only make schools a place for the transfer of knowledge in general or ethics but have not fulfilled the stage of forming ethics and morals. TMI Al-Amien Prenduan is an integrated learning system Islamic boarding school in Sumenep where the process of forming the character of students at TMI Al-Amien is basically directly applied in real life through daily activities. This study aims to determine the efforts and supporting and inhibiting factors in the formation of the character of students through habituation of discipline in Islamic boarding school activities at TMI Al-Amien Prenduan Sumenep. This study uses a descriptive qualitative approach. Collecting data with interviews, observation and documentation. Data analysis performs data condensation, presents data, draws conclusions. The results of the study show that: Efforts in the formation of the character of students through habituation of the discipline of Islamic boarding school activities at TMI Al-Amien Prenduan Sumenep are through the stages: planning, implementation, controlling, evaluating. Supporting and inhibiting factors in the formation of the character of students, namely: Supporting Factors: Internal Factors, namely: Motivation and awareness of the students themselves and the background of the students, External Factors, namely: Ustadz Ustadzah, Active Management, Adequate facilities, and Conducive Environment.